Competition, Cooperation, and Creativity: The Political Economy of Workshops and Workshop Styles in Bamenda, Cameroon. Issue 2 (3rd May 2016) - Förster, Till
Abstract : Bamenda in English-speaking Cameroon has some 34 art workshops. Most of the workshops sell their works to a commercial audience and offer signboard painting as well as a couple of other genres of applied art. The competition is very high. Though most of the artists insist that they have an individual style, there are striking similarities between different workshops and the art that they produce as most artists were apprentices of others in the city. After having established an independent workshop, they are likely to reproduce the style with which they had become familiar. However, they also need to demonstrate that they are able to develop an individual style. Creativity in such an urban setting is a precarious balance between adaptation and resistance. This article examines the economic constraints and the agency of the artists who have situated themselves in this difficult environment.